Działalność Komunistycznej Partii Zachodniej Białorusi w województwie wileńskim w latach 1930-1935 - Łukasiewicz, Sergiusz (In Gremium. Studies in History, Culture and Politics, 2016)
The activity of the Communist Party of Western Belarus in Vilnius Voivodeship in the period between 1930-1935 The purpose of this paper is to explain the activities of the Communist Party of Western Belarus in the Vilnius Voivodeship during the first half of the 1930s. The author’s aim is to show the organization of communists, party platform, as well as practical side of the operations of CPWB and the actions of polish authorities taken towards subversive organization. Another purpose of author is to specify exceptional ethnic and religious mosaic of Vilnius region. The communist party tried to exploit various social and ethnic tensions, which was particularly easy during years of the Great Depression. Nevertheless, against projects of party activists, feelings of most of the regions inhabitants did not radicalize. It was effect of active policy of local authorities, which through constant invigilation and harsh repressions systematically undermined position of the communist movement.